A multiscale approach for spatially inhomogeneous disease dynamics - Markus Schmidtchen; Oliver T.C. Tse; Stephan Wackerle (Indonesian Bio-Mathematical Society, 2018)
In this paper we introduce an agent-based epidemiological model that generalizes the classical SIR model by Kermack and McKendrick. We further provide a multiscale approach to the derivation of a macroscopic counterpart via the mean-field limit. The chain of equations acquired via the multiscale approach is investigated, analytically as well as numerically. The outcome of these results provides strong evidence of the models' robustness and justifies their practicality in describing disease dynamics, in particularly when mobility is involved. The numerical results provide further insights into the applicability of the different scaling limits.